2014
DOI: 10.1186/1471-2164-15-1068
|View full text |Cite
|
Sign up to set email alerts
|

Limits on the reproducibility of marker associations with southern leaf blight resistance in the maize nested association mapping population

Abstract: BackgroundA previous study reported a comprehensive quantitative trait locus (QTL) and genome wide association study (GWAS) of southern leaf blight (SLB) resistance in the maize Nested Association Mapping (NAM) panel. Since that time, the genomic resources available for such analyses have improved substantially. An updated NAM genetic linkage map has a nearly six-fold greater marker density than the previous map and the combined SNPs and read-depth variants (RDVs) from maize HapMaps 1 and 2 provided 28.5 M gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 54 publications
2
44
0
Order By: Relevance
“…An Arabidopsis CCoAOMT mutant line displayed increased disease symptoms (SenthilKumar et al, 2010). CCoAOMT was also identified as a candidate gene in resistance to maize southern leaf blight from the NAM-GWAS analysis (Kump et al, 2011;Bian et al, 2014), suggesting a possible association between disease resistance and HR in this case.…”
Section: Discussionmentioning
confidence: 99%
“…An Arabidopsis CCoAOMT mutant line displayed increased disease symptoms (SenthilKumar et al, 2010). CCoAOMT was also identified as a candidate gene in resistance to maize southern leaf blight from the NAM-GWAS analysis (Kump et al, 2011;Bian et al, 2014), suggesting a possible association between disease resistance and HR in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Bian et al (2014) found an association between flowering time and southern leaf blight resistance among lines within the NAM population. Controlling for this association did not dramatically affect the number or identity of loci found associated with resistance, but it raises the question of pleiotropy and potential phenotypic trade-offs among traits in the measurement of quantitative disease resistance.…”
Section: Polygenic Architecture Of Quantitative Resistancementioning
confidence: 97%
“…imputed recombinants as described above); b i is a vector of the family-specific additive effects associated with locus i relative to B73; k is the number of significant loci in the final model selected via a stepwise selection and optimization process (Bian et al 2014); and e is the residual vector. Segregation for the masculinized ear tip traits was restricted to the B73 3 CML69 RIL population.…”
Section: Nam Joint Linkage Analysismentioning
confidence: 99%
“…where Y is a vector of BLUE values for each inbred line for a given phenotype; A is an incidence matrix relating RILs to their corresponding population p; m is a vector of population main effects; X i is an incidence matrix indicating that RIL's genotype score at locus i, and the elements of X i are estimated dosages of the non-B73 parental allele at SNP i (coded as "0" for lines homozygous for the B73 reference allele, "2" for homozygotes with the alternate parental allele, "1" for heterozygotes, and a noninteger between 0 and 2 for the imputed recombinants as described above); b i is a vector of the family-specific additive effects associated with locus i relative to B73; k is the number of significant loci in the final model selected via a stepwise selection and optimization process (Bian et al 2014); and e is the residual vector. Segregation for the masculinized ear tip traits was restricted to the B73 3 CML69 RIL population.…”
Section: Nam Joint Linkage Analysismentioning
confidence: 99%
See 1 more Smart Citation